Commentary: The potential of sleep research to contribute to our understanding on antisocial behaviour – a reflection on Brown, Beardslee, Frick, Steinberg and Cauffman (2022). (20th October 2022) - Rowe, Richard
Abstract : A growing body of work indicates that sleep problems are associated with antisocial behaviour in young people. This opens up the opportunity for interventions that improve sleep to reduce antisocial behaviour. Brown et al. (2022) provide important new leads that can help to target interventions, highlighting that the relationship may be most relevant to aggressive offending and that it is consistent across adolescence and young adulthood. The within‐individual design adopted in this study has a number of methodological strengths. This commentary evaluates the effectiveness of the approach in terms of accounting for confounding effects and addressing temporal ordering. Directions for future research to build on the target paper are considered.